If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x = 8x + 9 Reorder the terms: 9x = 9 + 8x Solving 9x = 9 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 9x + -8x = 9 + 8x + -8x Combine like terms: 9x + -8x = 1x 1x = 9 + 8x + -8x Combine like terms: 8x + -8x = 0 1x = 9 + 0 1x = 9 Divide each side by '1'. x = 9 Simplifying x = 9
| -5x+3/4=-1/3 | | -6k-4k=10 | | 4/7.00000014=x/5 | | 12-10-k=-36 | | 6(2x-1)-7(2x+3)=2(x-1)+2(x-3) | | 3x^2+12x=-9 | | 2+2k=8 | | 3/5=4.2/x | | -4(c+15)+(-1)=-9 | | -2a=3s-10 | | -8y-2=-7y-6 | | 38=22-(8-6t) | | 3/4x5/7 | | (28b-1)-9(3b+1)=-2 | | 19x+4+26x-4=180 | | y/4-6=-9 | | 12-4(2x+3y)= | | 6/d=3 | | 8v-5+1=-4 | | 240-83x=541 | | 3x+41-5x=3-8x+2 | | 1/4x+1/4x=8 | | k+4(2k-7)=-100 | | (3/4)/(5/7) | | 2-5p-3p=-6 | | 3/4/5/7 | | -2m-24=0 | | 2-5p-4p=-6 | | 48/60 | | y+1=6/5x+18/5 | | a+4+2a=-8 | | -8n+-4=-28 |